OFR-35(2)-73 Evaluation Of Mine Electrical Systems With Respect To Safety, Technology, Economics And Legal Considerations - Volume II - Appendix I - Expected Power Parameters For Continuous Mining Sections - Robert Stefanko (The National Institute for Occupational Safety and Health (NIOSH), 1973)
The following tables contain the average, maximum and minimum power parameter levels for several mining machines. Power factor is listed only for defined transducer output regions. The reasons for the undefined areas are provided in the Instrumentation Chapter. Several maximum voltage drops are included, and are computed from the no load line-to-line voltage: Again, the drops are from measurements at the low side of the load center. The machines are: Continuous Miners; F6A Alpine 76AM Jeffrey (d-c) 8CM Joy 8CM (10CM) Joy 9CM-2AH Joy loam Joy CU-43-2H Joy 2 each CM26H Lee-Norse CM28E Lee-Norse Shuttle Cars; 18SC Joy 48S Torkar (a-c) 2 - 10SC Joys input to rectifier 2 - 16SC Joys input to rectifier